2007
DOI: 10.1007/s10157-007-0494-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory features of hyponatremia-induced myopathy

Abstract: The present findings indicate that hyponatremia infrequently causes skeletal muscle disruption, and that there are two types of hyponatremia-induced myopathy, acute onset and slowly progressive onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 16 publications
(24 reference statements)
1
13
0
Order By: Relevance
“…In a previous study, the slowly progressive muscle damage was only observed in the elderly subjects. 8 However, this may be a reflection that the elderly were more prone to developing hyponatremia and not necessarily a risk factor for hyponatremia-associated hyper-CKemia.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In a previous study, the slowly progressive muscle damage was only observed in the elderly subjects. 8 However, this may be a reflection that the elderly were more prone to developing hyponatremia and not necessarily a risk factor for hyponatremia-associated hyper-CKemia.…”
Section: Discussionmentioning
confidence: 98%
“…6,18 In one non-selective case series, the commonest cause of hyponatremia-associated hyper-CKemia was SIADH followed by primary polydipsia and congestive cardiac failure. 8 Although hyponatremiaassociated hyper-CKemia with water intoxication has been reported in several case reports, some of these presentations are confounded by the presence of coexisting causes of muscular injury such as seizures, intensive exercise and illicit drug use. 19,20 In comparison to others, the present study found a larger number of patients who had hyper-CKemia in the setting of diuretic-related hyponatremia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Hyponatremia due to water intoxication and SIADH is reported to cause rhabdomyolysis. 12,13 Many conditions are associated with rhabdomyolysis however it is rarely associated with the Addisonian crisis. Hyponatremia due to any cause can result in convulsions, which in turn may lead to muscle breakdown and ultimately renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…Rhabdomyolysis has been reported in the setting of other causes of hyponatraemia, such as water intoxication and syndrome of inappropriate secretion of antidiuretic hormone (SIADH) (9,10). The degree of hyponatraemia has yet to be correlated with the incidence or severity of rhabdomyolysis.…”
Section: Discussionmentioning
confidence: 99%